Comparing alternative Phillips curve specifications: European results with survey-based expectations - Maritta Paloviita (Bank of Finland, 2005)
This paper examines inflation dynamics in Europe.Econometric specification tests with pooled European data are used to compare the empirical performance of the New Classical, New Keynesian and Hybrid specifications of the Phillips curve.Instead of imposing any specific form of expectations formation, direct measures, ie Consensus Economics survey data are used to proxy economic agents' inflation expectations.According to the results, the New Classical Phillips curve has satisfactory statistical properties.Moreover, the purely forward-looking New Keynesian Phillips curve is clearly outperformed by the New Classical and Hybrid Phillips curves.We interpret our results as indicating that the European inflation process is not purely forward-looking, and inflation cannot instantaneously adjust to changes in expectations.Consequently, even allowing for possible non-rationality in expectations, a lagged inflation term enters the New Keynesian Phillips curve for inflation dynamics in Europe.
URN:NBN:fi:bof-20140807185
Keywords: E31; C52; 330; Phillips curve; expectations; Europe